Department Placement Against Career Maturity of Class XI Students at MAN 3 Medan - Faradilla, Zalza Mei; Siregar, Alfin (Universitas Islam Negeri Raden Intan Lampung, 2023)
Career selection and preparation is one of the challenges in adolescent development. The majors are tailored to the interests, talents and abilities of students and aim to provide more targeted teaching to students which will have an impact on student career selection and preparation. However, in reality there are still many SMAl/MAl/SMK students who are not lazy enough to plan their future careers. To realize students who are able to plan their careers, career guidance and counseling services are needed. Counseling services in the field of career guidance are an integrated part of all educational activities aimed at helping students complete their studies. The purpose of this study was to determine how much influence the placement of majors has on the career maturity of class XI Man 3 Medan students. In this study, quantitative research methods and data analysis techniques used simple linear regression. The population of this study was 344 students of class XI Man 3 Medan, the samples were taken by simple random sampling and the samples taken were several students of class XI Man 3 Medan. The results of the study show that there is a significant relationship between placement of majors and career maturity. By conducting this research, it can be seen that the placement of majors greatly influences the career maturity of students in the future.